CB2受容体活性化を介したアレルギー疾患治療薬としてのβカリオフィレン（BCP）の可能性 - 野崎, 千尋; 朝日, 透; 細木, 春花 (日本薬理学会年会要旨集, 2023)
Beta caryophyllene (BCP) is one of the sesquiterpenes found abundantly in cannabis as well as other plants such as clove, rosemary, black pepper, and lavender. Past studies have shown this terpene has antioxidant and anti-inflammatory effects, which is believed to be mediated by cannabinoid receptor type 2 (CB2). Recent study showed the attenuation of aortic inflammation by BCP inhalation, which is abolished by the treatment of CB2 antagonist.CB2 receptor is the Gi/Go type GPCR majorly expressed on the immune-related cells throughout the body. Thus, CB2 has been reported to act as a regulator in the immune system, but not many researches has been conducted to see the therapeutic possibility of CB2 to treat e.g. autoimmune disease by their immune suppression properties. However, since BCP showed inflammatory suppression effect by inhalation, we expected that BCP might be able to attenuate other inflammatory responses, such as allergic diseases through CB2-mediated immune suppression. We therefore examined whether CB2 can suppress allergic responses, particularly by acute inhalation of BCP. The BCP inhalation attenuated sneezing and nose scratch in nasal allergy model mice. Further, the immune cell population of CB2-deficient mice shifted similarly to that of wild-type mice after BCP administration. Altogether, we propose that BCP could be a potential substance to cure allergic diseases.